De socio-ekonomische instellingen : provinciale stedebouw, ekonomische raden & planbureau - Rijmenans, Arnold; Arijs, Maurits; Beckers, R. (Brussel: BSP, 1974)
"door A. Rijmenans, M. Arijs en R. Beckers"